Darkstalker - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire. Legends., 2016)
Long before the SandWing and the Dragonet Prophecy, Darkstalker, half NightWing and half IceWing, is hatched under the three moons--born into a divided heritage, he is destined to become the most powerful and dangerous dragon Pyrhhia will ever know, and it will take the combined efforts of a SeaWing named Fatham and a NightWing seer named Clearsight to come up with a way to save all the kingdoms from his anger.